1997
DOI: 10.3109/08880019709030902
|View full text |Cite
|
Sign up to set email alerts
|

Serum Erythropoietin Levels in Patients with Beta Thalassemia Major and Intermedia

Abstract: Serum erythropoietin (EPO) levels were determined by radioimmunoassay in 37 beta-thalassemia patients, the phenotype being thalassemia major (TM) in 30 and thalassemia intermedia (TI) in 7. The control group consisted of 37 healthy children. The mean serum EPO levels were significantly higher in patients with both TM (215.1 +/- 144.5) and TI (53.8 +/- 40.2) compared with the control group (9.3 +/- 4.6). Although the mean hemoglobin (Hb) concentrations in the patients with TM and TI were similar (8.6 +/- 0.9 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…The mean value of hematocrit (Hct) in the patients with TM (18.70 ± 3.51%) was lower than those with TI (25.24 ± 4.19%) whereas the mean serum Epo levels were significantly higher in TM than TI patients. Moreover, it was found that an inverse correlation between the serum values of Epo and Hct was observed in both TI and TM patients 42,43 . In addition, these data were explained as serum Epo levels increased in all thalassemia patients, despite repeated transfusion.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The mean value of hematocrit (Hct) in the patients with TM (18.70 ± 3.51%) was lower than those with TI (25.24 ± 4.19%) whereas the mean serum Epo levels were significantly higher in TM than TI patients. Moreover, it was found that an inverse correlation between the serum values of Epo and Hct was observed in both TI and TM patients 42,43 . In addition, these data were explained as serum Epo levels increased in all thalassemia patients, despite repeated transfusion.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, these data were explained as serum Epo levels increased in all thalassemia patients, despite repeated transfusion. This is explained by the fact that multiple transfusions may modulate the response of serum Epo to the degree of anemia, resulting in increased Epo levels and independent anemia in the TM patients 42,43 . In addition, the mean serum level of Epo was found to be higher in the thalassemic patients than in the controls, but transfused subjects had lower pretransfusional serum concentrations of Epo than untransfused ones 44 .…”
Section: Discussionmentioning
confidence: 97%
“…Increased erythropoiesis in β‐thalassaemia/Hb E patients has been proposed to occur as compensation for the anaemic condition resulting from the loss of erythroid cells (Olivieri, 1999) as a consequence of ineffective erythropoiesis (Mathias et al , 2000). The anaemic state is believed to result in increased production of EPO, which drives the increased erythropoiesis, and increased levels of circulating EPO in thalassaemic patients have been reported in several studies (Nisli et al , 1997; Chaisiripoomkere et al , 1999; Paritpokee et al , 2002) and are consistent with the levels found in the patients in this study, which showed a 3‐ to 60‐fold elevation of EPO levels, with no observable relationship between EPO levels and either total haemoglobin or haemoglobin F levels (data not shown). As such, the central belief, that increased EPO (either directly or in synergy with other cytokines) results in increased erythropoiesis, in thalassaemic patients, remains largely unsupported and untested.…”
Section: Discussionmentioning
confidence: 99%
“…In thalassaemic patients, several reports suggest that serum Epo values are variable and do not correlate closely with the degree of anaemia. Some authors have demonstrated that serum Epo levels in thalassaemic patients do not show consistent correlation with clinical measures of erythropoietic activity (Camaschella et al ., 1996; Nisli et al ., 1997). In our reference group, an inverse correlation was observed between Hb/Epo in β‐thalassaemic patients, indicating adequate Epo production for the degree of anaemia.…”
Section: Discussionmentioning
confidence: 99%